Test Review: Current options in at-home language proficiency tests for making high-stakes decisions. (October 2020) - Isbell, Daniel R.; Kremmel, Benjamin
Administration of high-stakes language proficiency tests has been disrupted in many parts of the world as a result of the 2019 novel coronavirus pandemic. Institutions that rely on test scores have been forced to adapt, and in many cases this means using scores from a different test, or a new online version of an existing test, that can be taken at home. The switch to accepting at-home proficiency tests for high-stakes decisions raises many concerns for stakeholders, such as technological demands, exam security, and validity of score use. Along these lines, this thematic review addresses such concerns and features brief reviews of seven options in at-home proficiency testing: ACTFL Assessments, Duolingo English Test, IELTS Indicator, LanguageCert, TEF Express, TOEFL iBT Special Home Edition, and Versant. Considering at-home testing more broadly, we discuss key considerations for selecting an at-home test. We close with speculation on how at-home tests may shape language testing going forward: Beyond adapting to the current pandemic, at-home testing might address longstanding issues in access to language testing services and the representation of real-world communication practices in language tests.